(untitled) (Academicia Globe: Inderscience Research, 2022)
Today, Uzbekistan is one of the successfully developing countries in Central Asia. The digital reforms carried out in all economic sectors of the Republic of Uzbekistan are now showing positive results in the development of all public and public sectors. The article talks about the reforms carried out in the field of information security in the Republic of Uzbekistan and their analysis.